Factors affecting migration of vanillin from chitosan/methyl cellulose films - Sangsuwan J. (2014)
The diffusion kinetics and factors affecting the migration of vanillin from chitosan/methyl cellulose (Chi/MC) films into water, cantaloupe juice (CJ), pineapple juice (PJ), and citrate buffer adjusted to pH values of 3.5, 5, and 6.5 were studied. Vanillin was incorporated into the Chi/MC films to provide an inhibitory effect against microorganisms. Initial vanillin concentration in the films, temperature, and pH of extracting solvent impacted the migration behavior of vanillin. The diffusion coefficients (D) followed the Arrhenius equation and increased as temperature increased for all the solvents. As temperature rose, the rate increment of the diffusion of vanillin into pineapple juice was higher than that into water and cantaloupe juice. Films containing lower vanillin content had a higher diffusion coefficient than those containing high vanillin content. Migration of vanillin was affected by pH rather than acid concentration. Lower pH resulted in a higher migration rate. © 2009 Institute of Food Technologists®.